Correlation of cognitive impairment with constipation and renal failure - Eshkoor, Sima Ataollahi; Hamid, Tengku Aizan; Chan, Yoke Mun (Penerbit Universiti Kebangsaan Malaysia, 2016)
The improvement of health care support has greatly extended the average life expectancy over the last 50 years, which has increased the rate of cognitive decline consequently. The avoidance of risk factors such as toxins, stress and somatic diseases can be protective against the reduction of cognitive function in the elderly. This study aimed to determine the effects of socio-demographic factors, constipation and renal failure on cognitive status among 2322 samples who were the non-institutionalized Malaysian elderly. The multiple logistic regression analysis was applied to estimate the risk of such factors on cognitive decline in subjects. Approximately, 77.54% of samples experienced cognitive impairment. The results showed that advanced age (odds ratio (OR) = 1.03), Malay ethnic (OR= 2.15), constipation (OR= 3.31) and renal failure (OR= 4.42), significantly increased the risk of cognitive impairment in subjects (p<0.05). In addition, education (OR= 0.38) significantly reduced the risk. However, we concluded that age, Malay ethnic, constipation and renal failure increased the risk of cognitive impairment in subjects but education reduced the risk.